Monochloropropanediol and glycidyl esters in infant formula and baby food products on the Danish market: Occurrence and preliminary risk assessment. (April 2020) - Nguyen, Khanh Hoang; Fromberg, Arvid
Abstract: A GC/MS-MS method for determination of monochloropropanediol (MCPDEs) and glycidol (GEs) was developed, validated, and applied to analyze 60 infant formula and baby food products commercially available on the Danish market. The contaminants were quantifiable in almost all sample categories with the exception of fruit or vegetable based purees. The highest concentrations of 3-MCPDEs and 2-MCPDEs were found in a baby biscuit product at 102.6 μg/kg and 52.8 μg/kg, respectively. Meanwhile, a baby puff item contained GEs as high as 149 μg/kg. MCPDEs and GEs concentrations are well correlated with each other in all sample types except puffs and biscuits. Occurrence data suggested that GEs formation might have taken place during production of baby puffs by unknown mechanisms. Preliminary exposure and risk assessment showed no apparent risk of Danish infants to these chemicals in formula and baby foods. However, special attention should be paid when feeding babies with puffs or similar items due to their relatively high level of GEs. Highlights: 2- and 3-MCPDEs and GEs were analyzed in Danish infant formula and baby foods. Most products contained low levels of MCPDEs and GEs. Highest concentrations of MCPDEs were in baby biscuit and of GEs were in baby puff. GEs formation might take place during puff production. Consumption of infant formula does not cause an apparent risk for infants.